2013
DOI: 10.1002/oby.20282
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent exergame play for weight loss and psychosocial improvement: A controlled physical activity intervention

Abstract: Overweight and obese youth, who face increased risk of medical complications including heart disease and type II diabetes, can benefit from sustainable physical activity interventions that result in weight loss. This study examined whether a 20-week exergame (i.e. videogame that requires gross motor activity) intervention can produce weight loss and improve psychosocial outcomes for 54 overweight and obese African American adolescents. Participants were recruited from a public high school and randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(217 citation statements)
references
References 11 publications
5
207
0
5
Order By: Relevance
“…5 However, this study found no differences between the competitive condition (competing against a live partner) and a single-player condition, which is contrary to the hypothesis that social game play may be more beneficial than solitary play. 4,6,7 This may be explained by a study limitation: The cooperative group had a smaller playing area due to sharing the gaming space with their cooperator, which may have reduced activity in the cooperative group and confounded study findings…”
Section: Outcomes Of Cooperation Versus Competition In Exergamingmentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, this study found no differences between the competitive condition (competing against a live partner) and a single-player condition, which is contrary to the hypothesis that social game play may be more beneficial than solitary play. 4,6,7 This may be explained by a study limitation: The cooperative group had a smaller playing area due to sharing the gaming space with their cooperator, which may have reduced activity in the cooperative group and confounded study findings…”
Section: Outcomes Of Cooperation Versus Competition In Exergamingmentioning
confidence: 99%
“…5 This conjecture has been supported by research showing that children who play exergames socially report greater increases in perceived social support, self-esteem, motivation, and self-efficacy than do children who play individually. 5,6 Social or group videogame play has been found to encourage continued use of exergames, maximize physical activity, and increase energy expenditure. [4][5][6][7] For example, children in a 12-week exergaming intervention were physically active for longer durations when they played in a multiplayer group (a total of 901 minutes) than when they played at home alone (356 minutes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that exergaming primarily enhanced the elderly participants' dynamic balance measures in walking, single-leg standing and reaching tasks; their reaction times also improved significantly [16][17][18][19][38][39][40][41]. Staiono et al studied exergames for weight loss and psychosocial improvements in adolescents and concluded that exergames, especially when played cooperatively, can be an effective technological tool for weight loss among young people [42]. Kramer et al used exergames to improve balance and gait in multiple sclerosis (MS) patients, and wrote that "the integration of exergames seems to have a positive effect on adherence and is thus potentially beneficial for the long-term effectiveness of rehabilitation programs for MS patients" [43].…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80] These studies have varied in age group and how they have accounted for physical activity.…”
Section: Television Watchingmentioning
confidence: 99%